Comparison of Modes of Administration of Screens to Identify a History of Childhood Physical Abuse in an Adolescent and Young Adult Population - Angela Diaz; Ken Peake; Anne Nucci-Sack; Viswanathan Shankar (Ubiquity Press, 2017)
Background: Childhood physical abuse is a major public health issue with negative consequences to health and well-being manifested in childhood and adolescence, and persisting into adulthood. Yet much childhood physical abuse is not identified when it occurs and little is known about how to screen for it. Methods: To address this gap, the effectiveness of 4 modes of administration of screens to identify childhood physical abuse were compared in a sample of 506 adolescents and young adults aged 12-24 years seeking general health services at a primary care clinic. Comparisons were made between paper and pencil screen, audio computer-assisted self-interview screen, face-to-face structured screen (all 3 using the same measure), and face-to-face unstructured interview. Findings: Overall, 44.5% of the sample disclosed that they had been physically abused. Compared to paper and pencil screen, the odds of reporting physical abuse were 1.5 (95% confidence interval [CI]: 0.92, 2.58) and 4.3 (95% CI: 2.49, 7.43) higher among participants using face-to-face structured screen and face-to-face unstructured interview methods, respectively. The face-to-face unstructured interview identified significantly more reports than the paper and pencil screen. Conclusions: Although the unstructured interview was the most effective mode for screening for childhood physical abuse, additional research is needed to confirm whether this holds true in other health care settings. Further research should examine how a health provider's training, experience, and comfort level might influence the identification of physical abuse disclosure in primary care settings using face-to-face unstructured interview.